x/3 - y/2 + 3 = 0
x/2 + y/5 - 5 = 0
(2x - 3y)/6 + 3 = 0
(5x +2y)/10 - 5 = 0
2x - 3y + 18 = 0
5x + 2y - 50 = 0
x = (3y - 18)/2
5((3y - 18)/2) + 2y - 50 = 0
(15y - 90)/2 + 2y - 50 = 0
15y - 90 + 4y - 100 = 0
y = 10
x = (3y - 18)/2 = 12/2 = 6
Пошаговое объяснение:
даю совет сначало посмотри в инете
x/3 - y/2 + 3 = 0
x/2 + y/5 - 5 = 0
(2x - 3y)/6 + 3 = 0
(5x +2y)/10 - 5 = 0
2x - 3y + 18 = 0
5x + 2y - 50 = 0
x = (3y - 18)/2
5((3y - 18)/2) + 2y - 50 = 0
x = (3y - 18)/2
(15y - 90)/2 + 2y - 50 = 0
x = (3y - 18)/2
15y - 90 + 4y - 100 = 0
x = (3y - 18)/2
y = 10
y = 10
x = (3y - 18)/2 = 12/2 = 6
Пошаговое объяснение:
даю совет сначало посмотри в инете